The Application of the Concept “Paradigm” in Psychology - Petrosyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
The article is an attempt to understand the use of the concept of “paradigm” in psychology. The author shows that the usage of the term “paradigm” to describe exemplary psychological theories and concepts imply neither the development of the psychology in the manner of Kuhn’’s scientific revolution nor the change in the meaning of the concept of “paradigm”. According to the author, psychological paradigms in their structure and functions are similar to the paradigms of the natural sciences observed by Kuhn. Differences concern not just the nature paradigms, but the form of their development, shift, and transformation.